IMPLEMENTATION OF POLICIES SUSTAINABLE DEVELOPMENT IN INDONESIA - Muhammad Agus Umar (Peneliti.net, 2018)
Development is a process of change planned to improve various aspects of people's lives. Sustainable development in this research is defined as development that balances economic, social and environmental sectors. The purpose of this study is to examine the extent to which the implementation of sustainable development policies in Indonesia. The method used is descriptive analysis using literature study data. The results of the analysis show that from several development indicators that have been carried out in Indonesia that are connected with the concept of sustainable development, it can be stated that there is no balance between social, economic and environmental development. Indonesia must reduce the amount of pressure on the environment as a result of economic development.